2010
DOI: 10.3233/jad-2010-1390
|View full text |Cite
|
Sign up to set email alerts
|

PBT2 Rapidly Improves Cognition in Alzheimer's Disease: Additional Phase II Analyses

Abstract: PBT2 is a copper/zinc ionophore that rapidly restores cognition in mouse models of Alzheimer's disease (AD). A recent Phase IIa double-blind, randomized, placebo-controlled trial found that the 250 mg dose of PBT2 was well-tolerated, significantly lowered cerebrospinal fluid (CSF) levels of amyloid-beta42, and significantly improved executive function on a Neuro-psychological Test Battery (NTB) within 12 weeks of treatment in patients with AD. In the post-hoc analysis reported here, the cognitive, blood marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
245
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 357 publications
(258 citation statements)
references
References 18 publications
3
245
0
1
Order By: Relevance
“…In a phase 2a clinical trial of 78 patients, 12 weeks of PBT2 treatment caused a dosedependent lowering of cerebrospinal fluid Aβ and improved 2 measures of executive function at the highest dose in the study (250 mg) [216,217]. In a recent phase 2b clinical trial of 1 year's duration, PBT2 did not show favorable clinical outcomes.…”
Section: Clioquinol and Pbt2mentioning
confidence: 95%
“…In a phase 2a clinical trial of 78 patients, 12 weeks of PBT2 treatment caused a dosedependent lowering of cerebrospinal fluid Aβ and improved 2 measures of executive function at the highest dose in the study (250 mg) [216,217]. In a recent phase 2b clinical trial of 1 year's duration, PBT2 did not show favorable clinical outcomes.…”
Section: Clioquinol and Pbt2mentioning
confidence: 95%
“…The first phase two clinical trial with PBT2, an analog of clioquinol more effective as a zinc/copper ionophore, found no significant effect on the mini-mental state examination (MMSE), ADAS-cog, or neuropsychological test battery (NTB) composite, memory or executive scores compared to the placebo (Sampson et al 2012). However, the highest dose was well tolerated for 12 weeks and resulted in significantly lower cerebrospinal fluid Ab42 levels, and improved performance relative to baseline values on two executive function tests from the NTB (Faux et al 2010). While larger trials are required to further test the efficacy of PBT2, several novel compounds aimed at modulating zinc availability including targeted nanoparticles loaded with zinc or coupled to chelators are in the preclinical testing phase (Bush and Tanzi 2008;Liu et al 2009;Grabrucker et al 2011a).…”
Section: Therapies Aimed At Modulating Zinc Availabilitymentioning
confidence: 99%
“…Evidence regarding changes in the brain mineral distribution of AD patients is apparently conflicting (Schrag et al 2011b), and our understanding of the mechanisms regulating zinc distribution in the brain during normal development, aging, and disease remains incomplete. Nevertheless, preclinical studies and early clinical trials have provided encouragement for mineral targeted therapies in the treatment and prevention of AD (Constantinidis 1992;Ritchie et al 2003;Lannfelt et al 2008;Faux et al 2010). These include zinc supplementation as well as pharmaceutical approaches designed to alter zinc and copper distribution.…”
Section: Introductionmentioning
confidence: 99%
“…However, no compelling data can prove that this hypothesis is wrong (2,5), and no other theories indicate a clear path for AD drug development (4). Thus the amyloid hypothesis is still an important framework for AD drug development (1)(2)(3)(4)(5)(9)(10)(11)(12)(13)(14). Additionally, Kim and colleagues (15) recently reported that a 3D cell-culture model of human neural cells could recapture AD pathology.…”
mentioning
confidence: 99%